Celestial Flames: Rabi'ah Al-Adawiyah's Spiritual Journey Through Love - IT, Suraiya (Prodi Studi Agama-Agama, 2024)
By referring to God as the Beloved, Rabi'ah al-Adawiah, the first Sufi woman, articulated the relationship with the Divine in a way that has come to be recognized as uniquely Sufi. The love described in the Pattern of Rabi'ah is thought to be pure love for God; the lover must walk along the route of love in order to remember God alone, not Hell or Paradise. When Rabi'ah speaks of